Computational modelling of microwave tumour ablations. (June 2013) - Chiang, Jason; Wang, Peng; Brace, Christopher L.
Abstract Microwave tissue heating is being increasingly utilised in several medical applications, including focal tumour ablation, cardiac ablation, haemostasis and resection assistance. Computational modelling of microwave ablations is a precise and repeatable technique that can assist with microwave system design, treatment planning and procedural analysis. Advances in coupling temperature and water content to electrical and thermal properties, along with tissue contraction, have led to increasingly accurate computational models. Developments in experimental validation have led to broader acceptability and applicability of these newer models. This review will discuss the basic theory, current trends and future direction of computational modelling of microwave ablations.